Daur Nasyād Khitābah al-Mimbariyyah fī Tanmiyyah al-Ṡiqqah al-Nafsiyyah fī al-Tahadduṡ bi al-Lugah al-‘Arabiyyah laday Ṭullab al-Madrasah al-Ṡānawiyyah - Anwar, Syuhaila; Al Rasyid, Harun (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
The purpose of this study is to describe the activities of muhâdhoroh to build students' self-confidence in speaking Arabic. This type of research is qualitative with a case study type at Madrasah Aliyah Tahfidzul Qur'an Al UMM Smart Center Tembung. The research data in this study is the muhâdhoroh activity. The data collection methods used in this study are observation, interviews, and documentation. The data obtained is then analyzed using data reduction techniques and conclusion drawing. The subjects of this study are the teachers and students at the Senior High School level of the Al-Umm Smart Centre for Qur’an Memorization The results of this study show that the muhâdhoroh activity in developing students' self-confidence at the Madrasah Aliyah Tahfidzul Qur'an Al UMM Smart Center is quite effective in supporting the development of students' self-confidence. In its implementation, the muhâdhoroh activity is held twice weekly, specifically every Monday and Friday after the Zuhr prayer. It lasts approximately seven minutes and is carried out alternately between classes. The strategy implemented in the execution of the muhâdhoroh activity at the Madrasah Aliyah Tahfidzul Qur'an Al UMM Smart Center involves male and female teachers selecting the theme of the speech. Then, the students study and memorize it independently before presenting it. After the muhâdhoroh activity is completed, the male and female teachers immediately evaluate the students' performance by explaining the aspects that need improvement, to develop the students' Arabic language skills for the future. There is no doubt that this muhâdhoroh activity has a significant and positive impact on the students, especially in building their self-confidence in speaking Arabic.